2019
DOI: 10.1080/15384101.2019.1577651
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle and cleavage events during in vitro cultivation of bloodstream forms of Trypanosoma lewisi, a zoonotic pathogen

Abstract: Trypanosoma (Herpetosoma) lewisi is a globally distributed rat trypanosome, currently considered as a zoonotic pathogen; however, a detailed understanding of the morphological events occurring during the cell cycle is lacking. This study aimed to investigate the cell cycle morphology and cleavage events of Trypanosoma lewisi (T. lewisi) during in vitro cultivation. By establishing in vitro cultivation of T. lewisi at 37°C, various cell morphologies and stages could be observed. We have provided a quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Although T. lewisi has been recognized as an opportunistic zoonotic blood parasite ( 12 ), very little was known about its cellular and genetic features until recent studies described its maxicircle genome ( 34 ) and its complex cell cycle ( 61 ). In this study, we investigated the organization of the T. lewisi minicircles, analysed the maxicircle and minicircle transcripts, as well as their editing and processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although T. lewisi has been recognized as an opportunistic zoonotic blood parasite ( 12 ), very little was known about its cellular and genetic features until recent studies described its maxicircle genome ( 34 ) and its complex cell cycle ( 61 ). In this study, we investigated the organization of the T. lewisi minicircles, analysed the maxicircle and minicircle transcripts, as well as their editing and processing.…”
Section: Discussionmentioning
confidence: 99%
“…To simplify the comparison between different cell cycles, it is helpful to use cell cycle proportion as a unit instead of an actual time, which also eliminates possible differences in enzymatic activities. Using this approach, the synthesis time for kDNA is as follows: T. lewisi (0.21 U) ( 61 ), T. cruzi (0.10 U) ( 77 ), Leishmania mexicana (0.41 U) ( 78 ), C. fasciculata (0.16 U) ( 79 ) and T. brucei (0.12 U in the procyclic stage) ( 80 ). Due to the lack of cell cycle studies in many life cycle stages, we simply consider that the synthesis time for kDNA is similar for all of them.…”
Section: Discussionmentioning
confidence: 99%
“…Additional cytokinesis events occur during epimastigote development in the tsetse fly; T. brucei proventricular cells undergo an asymmetric division to produce long and short epimastigote daughters (Van Den Abbeele et al, 1999); in contrast, T. congolense remodels to form epimastigotes (Peacock et al, 2018). Short epimastigotes can divide to produce two epimastigote daughters [ T. brucei, T. congolense, T. vivax , and T. lewisi (a rat trypanosome transmitted by fleas)], divide asymmetrically to give epimastigote and pre-metacyclic trypomastigote daughters ( T. brucei, T. vivax , and T. congolense ) or interconvert to trypomastigotes ( T. lewisi ) (Van Den Abbeele et al, 1999; Gluenz et al, 2008; Peacock et al, 2012, 2018; Rotureau et al, 2012; Ooi et al, 2016; Zhang et al, 2019a,c). While epimastigote furrow ingression appears to progress from anterior to posterior in all species, as in bloodstream and procyclic T. brucei , there are some notable differences in abscission.…”
Section: Cytokinesis In the Excavatamentioning
confidence: 99%
“…Further, the mother cell rapidly divides again, while still attached to its first daughter, resulting in a rosette of three cells; daughter cell motility is thought to ensure final severing of the link to the mother cell (Peacock et al, 2018). T. lewisi epimastigotes also undergo several rounds of cell division without completing cytokinesis, rapidly forming rosettes with 5–6 cell bodies attached at their posterior ends, from which, periodically, a fully segmented cell is released (Zhang et al, 2019c).…”
Section: Cytokinesis In the Excavatamentioning
confidence: 99%
“…Several days are needed to detect the parasites in blood and the prepatent period varies according to the parasite load [ 66 ]. Recent in vitro studies have also demonstrated the presence of further stages of development and multiplication, such as the “rosette” stage (multiple divisions forms) and the trypomastigote [ 178 ].…”
Section: Trypanosoma Species Naturally Occurrinmentioning
confidence: 99%